Pathogens That Cause Acute Febrile Illness Among Children and Adolescents in Burkina Faso, Madagascar, and Sudan. (2nd April 2021) - Marks, Florian; Liu, Jie; Soura, Abdramane Bassiahi; Gasmelseed, Nagla; Operario, Darwin J; Grundy, Brian; Wieser, John; Gratz, Jean; Meyer, Christian G; Im, Justin; Lim, Jacqueline Kyungah; von Kalckreuth, Vera; et al.
Abstract: Background: The etiology and optimal clinical management of acute febrile illness (AFI) is poorly understood. Methods: Blood samples taken from study participants with acute fever (≥37.5°C) or a history of fever and recruited into the previous Typhoid Fever Surveillance in Africa (TSAP) study were evaluated using a polymerase chain reaction (PCR)-based TaqMan-Array Card designed to detect a panel of bacterial, viral, and parasitic pathogens. Clinical metadata were also assessed. Results: A total of 615 blood samples available for analysis originated from Burkina Faso (n = 53), Madagascar (n = 364), and Sudan (n = 198) and were taken from participants ranging in age from 0–19 years. Through the TaqMan-Array Card, at least 1 pathogen was detected in 62% (33 of 53), 24% (86 of 364), and 60% (118 of 198) of specimens from Burkina Faso, Madagascar, and Sudan, respectively. The leading identified pathogen overall was Plasmodium spp ., accounting for 47% (25 of 53), 2.2% (8 of 364), and 45% (90 of 198) of AFI at the respective sites. In Madagascar, dengue virus was the most prevalent pathogen (10.2%). Overall, 69% (357 of 516) of patients with clinical diagnoses of malaria, respiratory infection, or gastrointestinal infection were prescribed a World Health Organization guideline-recommended empiric antibiotic, whereas only 45% (106 of 237) of patients with pathogens detected were treated with an antibiotic exerting likely activity. Conclusions: A PCR approach for identifying multiple bacterial, viral, and parasitic pathogens in whole blood unveiled a diversity of previously undetected pathogens in AFI cases and carries implications for the appropriate management of this common syndrome. Abstract : Children and adolescents with acute febrile illness at 3 African sites underwent testing for multiple bacterial, viral, and parasitic pathogens in whole blood, revealing a diversity of pathogens with important implications for appropriate management of this common syndrome.